TWO PERSPECTIVES ON THE RECENT WAR IN IRAQ - Beukes, Tobie (Scientia Militaria - South African Journal of Military Studies, 2015)
The three books discussed here can all be classified as memoirs or even as auto-ethnographies. The two authors relate how they experienced the recent armed conflict in Iraq. The narratives of both authors include detailed accounts of the extraordinary efforts they made to help Iraqi friends leave the country. Although Ashcroft and Johnson view the war from two very different perspectives, their narratives complement each other and can be read together profitably. Researchers and scholars with a focus on contemporary armed conflict should nevertheless find them well worth reading. This review explains why.